2014
DOI: 10.1089/lap.2014.0151
|View full text |Cite
|
Sign up to set email alerts
|

Single-Port Laparoscopic Distal Pancreatectomy: Initial Experience

Abstract: Blood loss and postoperative complications of single-port laparoscopic distal pancreatectomy are similar to those of conventional laparoscopic distal pancreatectomy. Single-port laparoscopic distal pancreatectomy can be performed safely and effectively in select patients with pancreas tail neoplasms, but is associated with a longer surgery time and postoperative hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The search strategy yielded 411 articles and we checked the title and abstract of the studies according to the inclusion and exclusion criteria and selected 53 articles. After the full texts of the remaining articles were read, 15 articles were included in the meta-analysis of MI-SPDP versus MI-DPS [13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 15 articles were included in the meta-analysis of MI-SVP versus MI-WT [13,23,[31][32][33][34][35][36][37][38][39][40][41][42][43]. Figure 1 shows the flow diagram of study identification and evaluation during the review process.…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy yielded 411 articles and we checked the title and abstract of the studies according to the inclusion and exclusion criteria and selected 53 articles. After the full texts of the remaining articles were read, 15 articles were included in the meta-analysis of MI-SPDP versus MI-DPS [13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 15 articles were included in the meta-analysis of MI-SVP versus MI-WT [13,23,[31][32][33][34][35][36][37][38][39][40][41][42][43]. Figure 1 shows the flow diagram of study identification and evaluation during the review process.…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences in intraoperative blood loss, tumor size, conversion rate, or postoperative complications between the two groups. 48 However, Yao et al and Haugvik et al reported that there were no significant differences in operative time, estimated blood loss, postoperative pain, and the length of postoperative hospital stay, even more so in the S-LDP group. 45,47 Most of the current research include retrospective studies or case reports; thus, the advantages of S-LDP require further exploration.…”
Section: Types and Outcomes Of Ldpmentioning
confidence: 94%
“…At present, most studies suggest that S-LDP is safe and feasible. 11,38,[45][46][47][48] Han reported that the mean operative time and mean duration of hospital stay in the S-LDP group were significantly longer than in the LDP group. The spleen was preserved more in the C-LDP group than in the S-LDP group, but this difference was not found to be significant.…”
Section: Types and Outcomes Of Ldpmentioning
confidence: 98%
“…Among them, 12 publications described individual patient short-term perioperative outcomes, and a total of 58 patients were selected to evaluate perioperative outcomes after LSP/LRP-DP (Table 2). There were four retrospective [9][10][11][12] comparative analyses between LSP/LRP-DP and conventional LDP. The most frequently used surgical system for LRP-DP was single-port with an additional 2-mm or 5-mm assist port.…”
Section: Currently Available Surgical Platforms and Short-term Outcomesmentioning
confidence: 99%
“…11 Among them, two 10,11 were reported by members of Korean Society of Endoscopic and Laparoscopic Surgery (KSELS). 14 The perioperative outcomes investigated in each study are summarized in Table 4.…”
Section: Comparative Analysis Between Lsp/ Rp-dp and Conventional Ldpmentioning
confidence: 99%